APLIKASI UREA DAN KOMPOS KULIT KAKAO UNTUK MENINGKATKAN KETERSEDIAAN DAN SERAPAN N, P, K SERTA PRODUKSI TANAMAN SAWI PADA INCEPTISOL TULUNGREJO, BATU - Putri Astria; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2017)
Cocoa pod husk is potential organic matter source to improve soil fertility as it contains relative high nitrogen and potassium. The objective of this study was to explore the effect of urea and cocoa pod husk compost application on availability of N, P, and K, uptake of N, P and N, and yield of mustard in an Inceptisol. Treatments tested were K0 = control, K1 = 100% Urea, K2 = 75% Urea and 25% cocoa pod husk compost, K3 = 50 % Urea and 50% cocoa pod husk compost, K4 = 100% cocoa pod husk compost, and K5 = 200% cocoa pod husk compost. Results of this study showed that application of 75 % Urea (163.05 kg ha-1) and 25% cocoa pod husk compost (2.717 Mg ha-1 ) increased available N of 230.43%, available P of 26.10 mg kg-1, and available K of 0.95 cmol kg-1 in the soil studied. Application of 200% cocoa pod husk compost (21.739 t ha-1) resulted in the highest organic C (2.17%) and pH (5.58). The highest N uptake by mustard plant (16.44 mg plant-1) was obtained from 100% Urea (217.40 kg ha-1 ) treatment. Application of 75% Urea and 25% cocoa pod husk compost produced the highest P uptake (3.08 mg plant-1), K uptake (6.39 mg plant-1), leaf area (635.46 cm2 plant-1), fresh weight (48.57 g plant-1 ) and dry weight (2.35 g plant-1), which were not significantly different with the application of 100% Urea.